Non-trivial frames for f(T) theories of gravity and beyond - Ferraro, R. (2011)
Some conceptual issues concerning f(T) theories - a family of modified gravity theories based on absolute parallelism - are analyzed. Due to the lack of local Lorentz invariance, the autoparallel frames satisfying the field equations are evasive to an a priori physical understanding. We exemplify this point by working out the vierbein (tetrad) fields for closed and open Friedmann-Robertson-Walker cosmologies. © 2011 Elsevier B.V.